2014
DOI: 10.1016/j.neubiorev.2013.12.004
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of sex differences in human brain structure

Abstract: HighlightsThis is the first meta-analysis of sex differences in the typical human brain.Regional sex differences overlap with areas implicated in psychiatric conditions.The amygdala, hippocampus, planum temporale and insula display sex differences.On average, males have larger brain volumes than females.Most articles providing sex differences in volume are in the ‘mature’ category.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

67
718
19
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 995 publications
(812 citation statements)
references
References 173 publications
(61 reference statements)
67
718
19
8
Order By: Relevance
“…We found that the PT as defined by the HO atlas showed the strongest sexually dimorphic asymmetry of any cortical region, which remained significant when adjusted conservatively for multiple testing over all cortical regions. Males showed stronger leftward PT regional lateralisation than females, which was consistent with some of the larger, previous studies where a sex difference has been reported (de Courten-Myers, 1999;Good et al, 2001;Shapleske et al, 1999; see also a recent study by Ruigrok et al (2014) showing females to have larger volumes of the right PT than males). The same sexual dimorphism in PT AI that we observed in BIG was also found in the two SHIP datasets, comprised primarily of older adults from north Germany, which totalled 1823 subjects.…”
Section: Asymmetry Of the Pt Is Sexually Dimorphicsupporting
confidence: 90%
“…We found that the PT as defined by the HO atlas showed the strongest sexually dimorphic asymmetry of any cortical region, which remained significant when adjusted conservatively for multiple testing over all cortical regions. Males showed stronger leftward PT regional lateralisation than females, which was consistent with some of the larger, previous studies where a sex difference has been reported (de Courten-Myers, 1999;Good et al, 2001;Shapleske et al, 1999; see also a recent study by Ruigrok et al (2014) showing females to have larger volumes of the right PT than males). The same sexual dimorphism in PT AI that we observed in BIG was also found in the two SHIP datasets, comprised primarily of older adults from north Germany, which totalled 1823 subjects.…”
Section: Asymmetry Of the Pt Is Sexually Dimorphicsupporting
confidence: 90%
“…In the present study, natal men relative to natal women and transgender men differed in resting-state measures in IFG thus being consistent with this prior work. Moreover, resting-state activity between men and women also differed in the left precentral gyrus (BA6), an area that has been found larger in men than in women (Ruigrok et al, 2014). Interestingly, whereas resting activity of the IFG differed between transgender men and their gender identity, in the precentral gyrus, transgender men differed from natal women in LFF, an effect that was supported by positive correlations with androgens in this structure.…”
Section: ! "#!mentioning
confidence: 78%
“…Sexual dimorphism in the frontal cortex has been observed in a variety of settings. For example, inferior frontal gyrus volume (IFG, BA44/45) is modulated by the androgen receptor (AR) gene in women (Raznahan et al, 2010), IFG is larger in women than in men (Ruigrok et al, 2014), and is an area that displays sex differences in activation patterns in prefrontally-mediated tasks such as verbal fluency (Gauthier et al, 2009). In the present study, natal men relative to natal women and transgender men differed in resting-state measures in IFG thus being consistent with this prior work.…”
Section: ! "#!mentioning
confidence: 99%
See 1 more Smart Citation
“…> Dans l'espèce humaine, des différences entre sexes ont été observées à différents niveaux : les capacités cognitives [1], la structure du cerveau [2] et l'activité cérébrale associée à l'exécution de tâches cognitives ou émotionnelles [3]. Cependant, les mécanismes exacts impliqués dans la différenciation sexuelle du cerveau et du comportement chez l'homme sont encore fortement discutés.…”
unclassified